Effects of alkali treatments on the tensile properties of pineapple leaf fibre reinforced high impact polystyrene composites - Siregar, Januar Parlaungan; Salit, Mohd Sapuan; Ab Rahman, Mohamad Zaki; Mohd Dahlan, Khairul Zaman (Universiti Putra Malaysia Press, 2012)
A study on the effects of alkali treatment and compatibilising agent on the tensile properties of pineapple leaf fibre (PALF) reinforced high impact polystyrene (HIPS) composite is presented in this paper. The tensile properties of natural fibre reinforced polymer composites are mainly influenced by the interfacial adhesion between the matrix and the fibres. In this study, several chemical modifications were employed to improve the interfacial matrix-fibre bonding and this resulted in the enhancement of tensile properties of the composites. In this study, the surface modification of pineapple fibre with alkali treatments and compatibilizer were used to improve the adhesion between hydrophilic pineapple fibre and hydrophobic polymer matrix. There are two concentrations of NaOH treatments and compatibilizer used in this study, namely, 2 and 4 wt. %. The results show that the alkali treated fibre and the addition of compatibilising agent in PALF/HIPS composites have improved the tensile strength and tensile modulus of the composites.